Minimal Socialization to the Community Regarding Legal Requirements for Working Abroad Causes an Increase in Human Trafficking of Workers from East Nusa Tenggara - Bait, Intan Yuningsi Puspitasari; Mustika, Arinda Diah Nur; Wibowo, Ari; Ferdiyansyah, Imam Denis; Krisdiyanto, Ahmad; Nawipa, Stepanus; Wangge, Ketrina Novika; Ama, Jefrianus Tamo; Kadir, Syukron Abdul (Journal of Legal and Cultural Analytics, 2024)
Every Indonesian citizen has the right to get a decent job as stated in the 1945 Constitution of the Republic of Indonesia Article 27 paragraph (2), however, due to limited job opportunities in Indonesia, many Indonesian citizens choose to work abroad. Therefore, the government has facilitated access to work abroad. Then, because of the increasing number of cases of human trafficking that occur among workers from Indonesia which is caused by the massive distribution of illegal labor, there are also legal regulations that regulate this matter, namely Law Number 21 of 2007 concerning Eradication of the Criminal Act of Trafficking in Persons and Government Regulation Number 46 of 2015 concerning Handling Victims of Human Trafficking Crimes. The method used is normative juridical research which focuses on das sein and das sollen, accompanied by data analysis of human trafficking cases to find out the factors of increasing cases of human trafficking in workers in Indonesia, then provide solution suggestions for the government to reduce the problem of illegal labor distribution. with a mass outreach program to the public containing an explanation of the legal protection of migrant workers, the risks of illegal workers, as well as legal conditions for working abroad.